Reductive Coupling of Diynes at Rhodium Gives Fluorescent Rhodacyclopentadienes or Phosphorescent Rhodium 2,2'-Biphenyl Complexes - Sieck, C.; Tay, M.G.; Thibault, M.-H.; Edkins, R.M.; Costuas, K.; Halet, J.-F.; Batsanov, A.S.; Haehnel, M.; Edkins, K.; Lorbach, A.; Steffen, A.; Marder, T.B. (Wiley-VCH Verlag GmbH & Co., 2016)
Reactions of [Rh(κ2-O,O-acac)(PMe3)2] (acac=acetylacetonato) and α,ω-bis(arylbutadiynyl)alkanes afford two isomeric types of MC4 metallacycles with very different photophysical properties. As a result of a [2+2] reductive coupling at Rh, 2,5-bis(arylethynyl)rhodacyclopentadienes (A) are formed, which display intense fluorescence (Φ=0.07-0.54, τ=0.2-2.5ns) despite the presence of the heavy metal atom. Rhodium biphenyl complexes (B), which show exceptionally long-lived (hundreds of μs) phosphorescence (Φ=0.01-0.33) at room temperature in solution, have been isolated as a second isomer originating from an unusual [4+2] cycloaddition reaction and a subsequent β-H-shift. We attribute the different photophysical properties of isomers A and B to a higher excited state density and a less stabilized T1 state in the biphenyl complexes B, allowing for more efficient intersystem crossing S1→Tn and T1→S0. Control of the isomer distribution is achieved by modification of the bis- (diyne) linker length, providing a fundamentally new route to access photoactive metal biphenyl compounds.